Awareness on Use of Anabolic Steroids Among Basketball Players in Tirupur- A Survey - A, ROSHAN; GANAPATHY, DHANRAJ; SASANKA, L. KEERTHI (The journal of contemporary issues in business and government, 2020)
Anabolic steroids, also known more properly as anabolic–androgenic steroids (AAS) are steroidal androgens that include natural androgens like testosterone as well as synthetic androgens that are structurally related and have similar effects to testosterone. Health risks can be produced by long-term use or excessive doses of AAS. Therefore, the aim of this present survey was to create awareness about usage of anabolic steroids among basketball players in tirupur. Self administered questionnaire was designed about awareness of usage of anabolic steroids among the population of basketball players. The questionnaires were distributed through a survey planet link and 172 subjects answered this survey. Data was collected and results were represented in pie charts. Results showed that 58.70% participants were aware that usage of anabolic steroids leads to a compensated life and 41.30% of the participants were not aware about it. Majority of participants 72.70% were not aware about different methods of intake of anabolic steroids and About 52.70% participants are not aware that anabolic steroids cause cardiac and liver disorders. It concludes that there is a moderate awareness about use of anabolic steroids and its complications among the participants. So , more awareness might be required about anabolic steroids in further studies among the general population to lead a healthy life.